Thinking about How We Think: Promoting Museum Literacy Skills with Metacognition. (2nd October 2018) - Sims, Sarah
ABSTRACT: Like many museums, the Missouri Historical Society wants to empower students to engage with history on their own terms. In our quest to create museum literate learners and push the student-centered field trip model to its maximum, we've internalized the crucial role of metacognition, or how we facilitate opportunities for students to think about their own thinking. With so many artifacts to encounter and stories to engage with, taking time for kids to reflect on what they are doing and how they are doing it seems like it should be a low priority. But we've found that metacognition is the most important part of our tours. This article will briefly outline the basics of metacognition; describe why and how metacognitive practices are woven into school programs at the Missouri Historical Society; and finally, it will take a look at the impact metacognition has on students participating in our programs.